Study of role of bacterial vaginosis in pelvic inflammatory disease, infertility and preterm labor - Amit A Rangari; Arun Jakhar (International Journal of Medical Research and Review, 2015)
Background and Objective: Prevention is better than cure. Bacterial vaginosis (BV) is associated with a two fold increased risk of preterm birth but its role in upper genital tract infection (pelvic inflammatory disease), tubal damage and infertility is less certain. Our study aimed at detecting the incidence of BV in infertility, preterm labour and pelvic inflammatory disease (PID).Material and Methods: Study comprised of 50 preterm labor women subjects, 12 infertile women subjects and 12 women subjects with pelvic inflammatory disease. Gram staining, Giemsa staining, KOH mount, pH determination of vaginal swabs from posterior fornix of women subjects of reproductive age(15 – 45 years) group who attended Gynaecology and Obstetrics OPD/IPD of our tertiary care hospitals were carried out.Results: Of the 50 preterm labor cases, 10 % (5) cases were of asymptomatic BV, 46% (23) case where of symptomatic BV. Of the 12 infertile women, 50% (6) cases were diagnosed to have BV. Of the 12 women with PID, 83 %( 10) cases were diagnosed to have BV.Conclusion: Most of the complications due to BV like pelvic inflammatory disease, infertility, preterm labor can be prevented if BV is diagnosed early and treated. In view of the potentially serious complications associated with BV, a routine screening of these patients is essential and simple tests like Gram Stain, Giemsa Stain, monitoring of pH should be recommended to be included as a routine screening test as part of Ante-Natal Care.